2018
DOI: 10.1002/pri.1708
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory exercise programme improves cognition and functionality in institutionalized older adults: A randomized control trial

Abstract: The multisensory exercise programme improved the cognition and functionality of institutionalized older adults. The introduction of a motor and multisensory-based approach in care routines may improve residents' health and engagement to the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 36 publications
1
49
0
13
Order By: Relevance
“…Some interventions for aging adults include bimanual coordination tasks such as multisensory exercise programs (Moreira et al, 2018); and juggling interventions (Draganski et al, 2004; Scholz et al, 2009). Results of a randomized controlled trial showed benefits from multisensory exercise training with bimanual hand movements to cognition and motor outcomes in institutionalized older adults (Moreira et al, 2018). In addition, neuroimaging data in adults who participated in a 90-day juggling intervention showed increased gray matter volume in the mid-temporal area bilaterally and in the left posterior intraparietal sulcus (Draganski et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some interventions for aging adults include bimanual coordination tasks such as multisensory exercise programs (Moreira et al, 2018); and juggling interventions (Draganski et al, 2004; Scholz et al, 2009). Results of a randomized controlled trial showed benefits from multisensory exercise training with bimanual hand movements to cognition and motor outcomes in institutionalized older adults (Moreira et al, 2018). In addition, neuroimaging data in adults who participated in a 90-day juggling intervention showed increased gray matter volume in the mid-temporal area bilaterally and in the left posterior intraparietal sulcus (Draganski et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research with older individuals, which has applied exercise for motor fitness and has resulted beneficial for mobility, has included both static or dynamic types of coordination and motor learning exercise, such as the adaptation of Tai-chi for frail individuals, mainly performed sitting and aiming at hand-eye-coordination [29,30,37,51], or more dynamically with mobility exercises with music [35,34,44]. A further approach applies the motor learning model which aims to stimulate the brain to learn the timing and sequence of movements through the repetition of a single movement until is automated [6].…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in this review contained a total of 667 participants ranging from 10 [28] to 68 [29] participants per study (table 2). The mean age of the study samples ranged from 133.5±26.9 months [30] to 84.8±4.1 years [31] . Two studies collected and reported information about multisensory exercise, which included participants all females [31,32] .…”
Section: Participants and Settingsmentioning
confidence: 99%
“…The mean age of the study samples ranged from 133.5±26.9 months [30] to 84.8±4.1 years [31] . Two studies collected and reported information about multisensory exercise, which included participants all females [31,32] . Of these participants, 30 were ataxic patients [33] , 73 were older adults with a history of falls [20,34,35] , 33 were older adults without fall history [35,36] , 18 were older adults with visual impairment [37] , 16 were diabetics with peripheral neuropathy [38] , and 21 were patients with essential tremor [39] .…”
Section: Participants and Settingsmentioning
confidence: 99%
See 1 more Smart Citation